1969
DOI: 10.1161/01.cir.39.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects of a New Antihypertensive Drug, Catapres (ST-155)

Abstract: Catapres is a new imidazoline compound with potent antihypertensive properties. Significant reduction in blood pressure occurs between 1 and 4 hours after oral administration, with the peak effect occurring at 2 to 4 hours and the antihypertensive effect extending for 6 to 10 hours. Blood pressure is reduced in both the supine and erect positions, although the orthostatic response is the more prominent.Cardiac output is reduced moderately in both the supine and erect positions. Peripheral vascular resistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 7 publications
3
33
0
Order By: Relevance
“…This has been exploited clinically by the development of pharmacological agents with ␣ 2 -agonistic properties (eg, clonidine) that suppress the central SNS and produce a sustained antihypertensive action. 12 However, existing ␣ 2 -agonists are nonselective for ␣ 2 -AR subtypes. Genetic targeting of each one of the ␣ 2 -AR gene subtypes has now produced evidence that suggests that the longrecognized sympathoinhibitory effect of central presynaptic ␣ 2 -AR may be a function of the ␣ 2A -AR subtype.…”
Section: Discussionmentioning
confidence: 99%
“…This has been exploited clinically by the development of pharmacological agents with ␣ 2 -agonistic properties (eg, clonidine) that suppress the central SNS and produce a sustained antihypertensive action. 12 However, existing ␣ 2 -agonists are nonselective for ␣ 2 -AR subtypes. Genetic targeting of each one of the ␣ 2 -AR gene subtypes has now produced evidence that suggests that the longrecognized sympathoinhibitory effect of central presynaptic ␣ 2 -AR may be a function of the ␣ 2A -AR subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also found (Barnett and Cantor, 1968;Muir et al, 1969) that the circulatory response to exercise is not affected by clonidine. Another desirable feature is that clonidine does not reduce renal blood flow or glomerular filtration rate (Onesti et al, 1969), so that, like methyldopa, it is suitable for treating renal hypertension. The five patients with renal hypertension in this study did not differ from the other patients in blood pressure response or dosage requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of clonidine have been reported from Europe (Bock et al, 1966;Frank and von Loewenich-Lagois, 1966;Grabncr et al, 1966;Kochsiek and Fritsche, 1966;Lieb and Ridders, 1966;Michel et al, 1966;Iisalo and Laurila, 1967), America (Davidov et al, 1967;Onesti et al, 1969;Smet et al, 1969), and Australasia (Ng et al, 1967;Raftos, 1969), and several workers have carried out acute haemodynamic studies (Barnett and Cantor, 1968;Muir et al, 1969). These show that clonidine lowers the blood pressure in all grades of hypertension, irrespective of posture.…”
Section: Introductionmentioning
confidence: 99%
“…Onesti and co-workers' (3) observation of a decrease in Ux,V in the absence of any change in RPF gave rise to their suggestion of a direct tubular action of catapres. In their study, RPF was estimated by CLIAII, a method that cioes not give total RBF.…”
mentioning
confidence: 93%